DESIGN OF PHYSICS TEACHING MATERIAL BASED GUIDED INQUIRY ON MOMENTUM AND IMPULSE MATERIALS TO SUPPORT CRITICAL THINKING SKILLS - Chakampai, Sanjung Pradana (Physics Learning and Education, 2024)
This research aims to analyze requirements that underlie design of teaching materials that can support the proficiency of critical thinking. This research explains how teachers and students understand about the learning model used in the classroom, gives a brief explanation of a preferred teaching materials teaching material, how the teaching material contributes to support students' critical thinking skills and literature analysis that supports the needs analysis. Method of this research is both of quantitative and qualitative methods. For teachers and students, several tools are used such as questionnaires and interview papers. The data of student research instruments include students' interest and motivation in learning physics, responses to the use of teaching materials in class, and responses to questions Critical thinking skills. The data of teachers include user of model learning process and teaching material used. Commonly, teaching materials are anticipated to additional spirit and motivation of student in learning so that they can support critical thinking skills. For this reason, teaching materials are integrated with a guided inquiry model and teaching materials that support students' critical thinking skills that are developed based on indicators of teaching material development.